A study on the perception and awareness towards attitude of parents on children vaccination / Azila Ahmad , Farah Amanina Ahmad Fozee and Umi Nadia Ahmad Rafaie - Ahmad, Azila; Ahmad Fozee, Farah Amanina; Ahmad Rafaie, Umi Nadia (2017)
Vaccination is one of the important commitments of health that everybody should focus on especially right after giving birth and having babies. Recently, there have been many issues on the necessary of getting the vaccine for children. Some of the parents choose not to allow their children to get vaccines as they assumed that vaccine is one of the harmful things. Yaqub et al. ( 2014) quoted from (Andre et al., 2008) stated that vaccines are widely known by health authorities and the medical community as an important tool for achieving public health achievement. Yet, people are still doubting the benefits of vaccines, worry over their assurance and still arguing about the need for getting vaccines, an attitude we refer to as vaccine hesitancy (Yaqub et al., 2014). Vaccines are unquestionably one of the most cost-effective instruments in the health system. It is cheaper although it presents tremendous benefits for the health and well-being of populations (Masadeh et al., 2014)